A Novel Ratiometric Fluorescent Probe for Highly Sensitive and Selective Detection of β‐Galactosidase in Living Cells. Issue 4 (26th February 2019) - Chen, Min; Mu, Lixuan; Cao, Xingxing; She, Guangwei; Shi, Wensheng
Summary of main observation and conclusion: β‐Galactosidase, a glycoside hydrolase enzyme, has been proved to be an important biomarker of cell senescence and primary ovarian cancer. Effective detection of β‐galactosidase has attracted wide attention. Herein, one ratiometric fluorescent probe has been successfully synthesized for detecting the β‐galactosidase in living cells. The as‐prepared probe exhibits two emission peaks at 490 nm and 530 nm, respectively, and the ratio of fluorescence intensities from the two emission peaks could be utilized to monitor the β‐galactosidase. This present ratiometric fluorescent probe is, therefore, very promising for effective, sensitive, and selective detection of the β‐galactosidase in living cells. Abstract : A novel ratiometric fluorescent probe for β‐galactosidase detection in living cells was designed and synthesized.